Concluding remarks: Faraday Discussion on chemistry in the urban atmosphere. (1st July 2016) - Jimenez, Jose L.
Abstract : This article summarises the Concluding remarks from the Faraday Discussion on Chemistry in the Urban Atmosphere. The following themes are addressed: (a) new results that inform our understanding of the evolving sources and composition of the urban atmosphere ("News"); (b) results that identify gaps in our understanding that necessitate further work ("Gaps"); (c) the emerging instrumentation revolution and some of the challenges that it brings; (d) the structural issues of insufficient support for the analysis of field campaigns; and (e) some important areas that were missing from this Faraday Discussion and that should receive an increasing focus in the future.